Mixed Cultural Representation of Stuart's Character in Minions As a Symbol of Strength and Protection: Mixed Cultural Representation of Stuart's Character in Minions As a Symbol of Strength and Protection - Zaini Ramdhan (JOMANTARA, 2021)
The myth of the one eye symbol is a symbol of the symbolism of symbols that are still unclear and hidden visual signs. Interpretations can be unclear and varied, Connecting with the sign of the Illuminati, the sun god with the eye symbol depicted single or one will have a psychological impact on the one who reads it. History records of artifacts made about the shape of the eye symbol and other forms. It is in ancient religious symbols of worship and leadership. The Sumerians demonstrated the sanctity of certain sculptures, the shape of the eyes enlarged by an abnormal size gave the impression, the message of sensation from the statue. Making performances of religious ceremonies, artists seek to bring sculptures to life in the way they do eye openings. The ancient Egyptian civilization was the originator of the disembodied eye as a symbol of the single eye. One of the well-known symbols of Egypt is the eye of the sun god in Pharaoh's mythology. The image is a mixture of the image of a human eye combined with an eagle's eye, with eyebrow markings, dark cheek markings of a bird. And also various forms of the relics of the modern era associated with the shape of the image of the one eye. In this case, Semiotics is a branch of science that studies a sign. Semiotics comes from the Greek word: semeion, which means sign. Sign as something that represents something; metaphor. The process of a sign as a representative occurs when the sign is reinterpreted concerning what it represents, in the form of visual forms, colors in works of art. It can be said that Semiosis is a process in which the sign becomes a function as a representative of the signified. The focus of researchers in the study of semiotics here is a visual sign of combining entities that are used as representations of the represented entities. This representation process is often called signification. This research is how the visual sign of the one eye on the animated minion character named Stuart can be a representation of the one eye symbol in the past and modern era that represents it both in shape and color.